Infecção experimental de Calomys callosus (Rodentia-Cricetidae) com Leishmania donovani chagasi (Laison, 1982) Experimental infection of Calomys callosus (Rodentia-Cricetidae) with Leishmania donovani - Dalva A. Mello; Maria Lucia Teixeira (Universidade de São Paulo, 1984)
Foi descrita a infecção experimental em Calomys callosus com uma cepa de Leishmania donovani chagasi de caso humano. Um grupo de 22 roedores foi inoculado por via intraperitoneal com 0,1 ml de um macerado de baço em salina, rico em amastigotas. Esses animais foram sacrificados três meses após as inoculações, tendo sido realizado: cultura "in vitro" em meio acelular (LIT e NNN) e esfregaços, corados pelo Giemsa, de fígado, baço, medula óssea e sangue; cortes histológicos corados com hematoxilina-eosina de fígado e baço. Os resultados para fígado e baço foram: 67% de positividade nas culturas "in vitro"; esfregaços ricos em amastigotas intra e extra celular (inclui medula óssea); reações teciduais traduzidas por hepatomegalia com proliferação das células de Kupffer; reação granulomatosa das áreas portais, esplenomegalia com reações granulomatosas, abundância de formas amastigotas. Os resultados para o sangue foram negativos em todas as investigações. In the current paper experimental infection of Calomys callosus with Leishmania donovani is reported for the first time. A group of 22 C. callosus aged 20 months and weighing 25 g were inoculated with 0.1 of a homogeneous saline preparation of infected spleens of homologous animals. The L. donovani strain used in the experiments was isolated from a case of human visceral leishmaniasis from the state of Maranhão, Brazil. The animals infected were weighed and killed 3 months after the experimental infection. Spleens and livers were also weighed and pieces from them were fixed in 10% formaline and stained with hematoxilin-eosin for histological studies. Impression smears stained with Giemsa were made and cultivation "in vitro" (NNN and LIT) was done, with material from blood, spleen, liver and bone marrow. At the end of the experiments the animals showed low of body weight. Splenomegaly was observed in all the inoculated animals. The "in vitro" cultures were positive from liver and spleen in 67% of the animals. Many extracellular and intracellular amastigote forms were seen in the smears of spleen, liver and bone marrow. Blood showed negative results. Histological studies of the liver showed proliferation of Kupffer cells and granulomatous reaction in the portal areas with multinucleated cells and amastigote forms of the parasites. Loss of folicular pattern with parasitism in great numbers of cells around which there were granulomatous reactions were observed in the spleen.